2020
DOI: 10.1093/ckj/sfaa077
|View full text |Cite
|
Sign up to set email alerts
|

The genetic map of diabetic nephropathy: evidence from a systematic review and meta-analysis of genetic association studies

Abstract: Despite the extensive efforts of scientists, the genetic background of diabetic nephropathy (DN) has not yet been clarified. To elucidate the genetic variants that predispose to the development of DN, we conducted a systematic review and meta-analysis of all available genetic association studies (GAS) of DN. We searched in the Human Genome Epidemiology Navigator (HuGE Navigator) and PubMed for available GAS of DN. The threshold for meta-analysis was three studies per genetic variant. The association between ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 48 publications
2
35
0
1
Order By: Relevance
“…80 The same variant of IL-4 and IL-6 genes were also associated with kidney function in the Japanese population. 81 In addition, GWAS variants in some other inflammation regulatory genes such as engulfment and cell motility protein 1 (ELMO1), TGF-β, TNF-α, CCR5, IL-1β, IL-8, IL-10, IL-18, MMP9, and TNF receptor-associated factor 6 are linked with the pathogenesis of DKD, 82,83 and some of these variants differ across populations. For instance, ELMO1-rs741301, ELMO1-rs10951509, and CCR5-rs1799987 in Chinese, ELMO1-intron 18+9170 in Japanese, TGF-β-rs1800470 in Chinese, Egyptians, and Mexicans, TGF-β-rs1800471 in Mexicans, and IL-8-rs4073 in Indians.…”
Section: Inflammatory Mediatorsmentioning
confidence: 99%
“…80 The same variant of IL-4 and IL-6 genes were also associated with kidney function in the Japanese population. 81 In addition, GWAS variants in some other inflammation regulatory genes such as engulfment and cell motility protein 1 (ELMO1), TGF-β, TNF-α, CCR5, IL-1β, IL-8, IL-10, IL-18, MMP9, and TNF receptor-associated factor 6 are linked with the pathogenesis of DKD, 82,83 and some of these variants differ across populations. For instance, ELMO1-rs741301, ELMO1-rs10951509, and CCR5-rs1799987 in Chinese, ELMO1-intron 18+9170 in Japanese, TGF-β-rs1800470 in Chinese, Egyptians, and Mexicans, TGF-β-rs1800471 in Mexicans, and IL-8-rs4073 in Indians.…”
Section: Inflammatory Mediatorsmentioning
confidence: 99%
“…A number of SNPs and their corresponding genes have been associated with DKD in several populations and studies. The engulfment and cell motility 1 (ELMO1) gene has shown an association with DKD in a Japanese population [ 29 ], a finding verified in a review and meta-analysis including both DM1 and DM2 populations of different origin [ 30 ]. The sterol regulatory element-binding protein-1 gene (SREBPF-1) has been also found to contribute to DM2 and DKD in a French, obese population suffering from DM2 as well as in mice [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 94%
“…Polymorphisms of the Transcription Factor 7-Like 2 (TCF7L2) gene have been associated with DM2 incidence in European and African-American populations, suffering from micro and macrovascular complications of DM2 including DKD [ 33 , 34 ]. The C677T variant of the methylenetetrahydrofolate reductase (MTHFR) gene on the metabolic pathway of homocysteine has been associated with DKD presentation and progression in DM2 populations of south Indian [ 35 ] and Tunisian origin [ 36 ] and in a meta-analysis including several studies [ 30 ]. Polymorphisms in the nonmuscle myosin IIA gene (MYH9) have been associated with ESKD susceptibility in a European American population with DM2 [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main factors triggering the dysregulation of DKD pathways comprehend persistent hyperglycemia, obesity-related factors, β-cell failure, and insulin resistance. Both murine and human studies demonstrated that the increased cellular sugar concentration is the primary trigger leading to ESRD progression [ 108 ].…”
Section: Pathogenic Mechanismsmentioning
confidence: 99%